2010
DOI: 10.1002/ppap.200900153
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene oxide)‐like Plasma Polymers Produced by Plasma‐Assisted Vacuum Evaporation

Abstract: Thermal decomposition of PEO under vacuum was used in combination with a glow discharge to deposit PEO‐like plasma polymer films. Evaporation without plasma allows the deposition of films with chemical composition very close to that of the original PEO, albeit with a lower average of molar mass. The application of plasma during vacuum evaporation leads to enhancement of crosslinking within the films, yet at the expense of reduced retention of ether structure. Non‐fouling properties and thrombogenicity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 40 publications
7
77
0
Order By: Relevance
“…PEG-like surfaces have also been prepared by plasma polymerization and/or deposition techniques [137][138][139]. These coatings have been revealed to reduce the adsorption of BSA, IgG, and Fbg [138,139].…”
Section: Peg-based Coatingsmentioning
confidence: 99%
“…PEG-like surfaces have also been prepared by plasma polymerization and/or deposition techniques [137][138][139]. These coatings have been revealed to reduce the adsorption of BSA, IgG, and Fbg [138,139].…”
Section: Peg-based Coatingsmentioning
confidence: 99%
“…Therefore, the monomers are low‐molar‐mass volatile substances. Nevertheless, it has been recently shown that vacuum thermal degradation of conventional polymers can be utilized as a source of higher molar mass species 4, 5. In this case, the polymer is heated under rarefied inert atmosphere to a temperature at which thermal decomposition of macromolecular chains occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Although low‐molar‐mass fragments are also released, they are effectively removed by the pumping system and do not participate in the film formation. Thus, the flux of emitted PEO oligomers is analogous to the flow of vapors of organic precursors, except that it does not consist of a single type species but is rather characterized by a distribution of molar masses, with the average exceeding 1 000 g · mol −1 4, 5. Oligomers released as a result of vacuum thermal degradation of PEO can condense on the substrate to form a polymeric film.…”
Section: Introductionmentioning
confidence: 99%
“…Such surfaces are defined as “non-fouling” or “anti-fouling” [42,43,44]. This property is believed to correlate strongly with the hydration layer at the PEO surface [45], attributed to the presence of hydrophilic ether (CH 2 -CH 2 -O) n .…”
Section: Non-fouling Plasma Deposited Coatingsmentioning
confidence: 99%